Chapter The production of international fashion in state-sponsored manufactures in Sweden-Finland, 1740-1810. Part I - Nyberg, Klas (Datini Studies in Economic History, 2022)
This paper discuss the production of international textiles in statesponsored manufactures in Sweden-Finland between 1740 and 1810. The data set is based on the general summaries of manufacture output collected by municipal authorities during this period. The summaries include annual data on the production of the most important wool and silk textiles, wool and silk knitwear, as well as cotton and linen textiles. More specifically the paper analyze the type of fashion that was produced in Swedish textile manufactures during the period and how international influences affected the Swedish product range. In a subsequent forthcoming investigation I will discuss what the change in the Swedish textile production range towards the end of the eighteenth century says about Swedish and Nordic textile fashion in a European and international context.